The nucleotide sequences of two leghemoglobin genes from soybean. - Wiborg, O (1982)
We present the complete nucleotide sequences of two leghemoglobin genes isolated from soybean DNA. Both genes contain three intervening sequences in identical positions. Comparison of the coding sequences with known amino-acid sequences of soybean leghemoglobins suggest that the two genes correspond to leghemoglobin C2 and leghemoglobin C3, respectively.